Influência de ventos, marés e mesoescala sobre os fluxos superficiais entre o talude e a plataforma continental SSE do Brasil - Bazoni Junior, Luciano (2017)
The influence of winds, tides and mesoscale on the surface flows between the SSE slope and continental shelf of Brazil was investigated using a Lagrangian model for particle transport, forced by results of numerical simulations in high resolution with HYCOM model. Three experiments were carried out: i) with tides, ii) without tides and iii) with winds acting directly on the advection of the particles. The surface launches were made at different sites on the continental margin. The flow of the Brazil Current (BC) and its mesoscale activity were more significant on the flows towards the ocean. Preferential regions for transport toward slope and ocean were those with a narrower continental shelf and where the occurrence of meanders and vortex is recurrent – Cabo de São Tomé, Cabo Frio and Santos. Direct action of the winds was more important for the transport towards the continental shelf, being able to surpass the flow of the BC, mainly in the southern part of the study area. The tides had little influence on the flows between slope and shelf. Seasonal variations of BC and winds, although little influence in general, have determined the predominance of flows in different regions.